Endangered Commons? Modeling the Effects of Demographic Trends Coupled with Admission Rules to Common Property Institutions - Cristina Dalla Torre; Rocco Scolozzi; Elisa Ravazzoli; Paola Gatto (Land)
This study investigates the long-term effects of demographic trends and admission rules on common properties in the Province of Trento, Italy, which we refer to as historical commons. Historical commons have evolved into socio-ecological systems over the centuries, meaning that communities governed collectively natural resources and lands essential for community survival. Communities and the admission rules that determine their composition are an important constituting element of historical commons because they have developed local ecological knowledge and practices of sustainable use of natural resources. Our study hypothesizes that commons continuity is endangered because of the declining trend of the size of communities being influenced by demographic trends coupled with admission rules. Grounding our research in systems dynamics, we use empirical data including demographic projections and existing admission rules to simulate their effect on the site of the community using the Province of Trento, Italy, as our study region. To achieve that, three types of historical commons are identified: open, semi-open, and closed, each with different admission criteria based on inheritance and/or residency. Results indicate that inheritance-based admission rules can significantly reduce the number of commoners over time, potentially endangering the continuity of these self-governance institutions. The study discusses the results in light of the literature on historical commons’ continuity to evaluate different policies affecting the size of the community grounding on different mental models. The study concludes that a simulation approach can promote an anticipatory approach to the co-design of policies to ensure inclusive continuity of historical commons.